Realitas Sosial Keluarga Batak Toba dan Relevansinya Terhadap Solidaritas Sosial di Kawasan Danau Toba - Harisan Boni Firmando (Universitas Muhammadiyah Sumatera Utara, 2021)
This study discusses the social reality of the Toba Batak family and its relevance to social solidarity. This study aims to understand the social reality of the Toba Batak family and the values of local wisdom so that social solidarity can be realized. The theory used in this research is the theory of social reality construction and structural functionalism theory. The method used in this research is a qualitative method with a descriptive approach. Data collection was carried out by means of observation, interviews, document study and focus group discussions, so that conclusions can be drawn. The results showed that the presence of the Toba Batak family could create social solidarity. The social reality of the Toba Batak family can be seen from the sociological and historical aspects of the life of the people in the Lake Toba area. Most people have a desire to live together in peace, marked by the adaptation of the values and norms and customs of the local community. This is strengthened by people who hold strong local wisdom values that teach people to help each other to help one another. Social solidarity is manifested in various forms of cooperation that are often carried out by the community, generally in the form of mutual cooperation and mutual assistance. Social solidarity is realized because of the good social interaction of community members and is bound by a kinship system dalihan na tolu.